Nutrient History Affects the Response and Resilience of the Tropical Seagrass Halophila stipulacea to Further Enrichment in Its Native Habitat - Helber, Stephanie B.; Winters, Gidon; Stuhr, Marleen; Belshe, E. F.; Bröhl, Stefanie; Schmid, Michael; Reuter, Hauke; Teichberg, Mirta (Frontiers in Plant Science, 2021)
Eutrophication is one of the main threats to seagrass meadows, but there is limited knowledge on the interactive effects of nutrients under a changing climate, particularly for tropical seagrass species. This study aimed to detect the onset of stress in the tropical seagrass, Halophila stipulacea, by investigating the effect of in situ nutrient addition during an unusually warm summer over a 6-month period. We measured a suite of different morphological and biochemical community metrics and individual plant traits from two different sites with contrasting levels of eutrophication history before and after in situ fertilization in the Gulf of Aqaba. Nutrient stress combined with summer temperatures that surpassed the threshold for optimal growth negatively affected seagrass plants from South Beach (SB), an oligotrophic marine protected area, while H. stipulacea populations from North Beach (NB), a eutrophic and anthropogenically impacted area, benefited from the additional nutrient input. Lower aboveground (AG) and belowground (BG) biomass, reduced Leaf Area Index (LAI), smaller internodal distances, high sexual reproductive effort and the increasing occurrence of apical shoots in seagrasses from SB sites indicated that the plants were under stress and not growing under optimal conditions. Moreover, AG and BG biomass and internodal distances decreased further with the addition of fertilizer in SB sites. Results presented here highlight the fact that H. stipulacea is one of the most tolerant and plastic seagrass species. Our study further demonstrates that the effects of fertilization differ significantly between meadows that are growing exposed to different levels of anthropogenic pressures. Thus, the meadow’s “history” affects it resilience and response to further stress. Our results suggest that monitoring efforts on H. stipulacea populations in its native range should focus especially on carbohydrate reserves in leaves and rhizomes, LAI, internodal length and percentage of apical shoots as suitable warning indicators for nutrient stress in this seagrass species to minimize future impacts on these valuable ecosystems.